Los derechos de los inversores extranjeros sobre la tierra según los tratados de protección de inversiones: una visión desde Latinoamérica (2016)
In the last ten years foreign investment in agriculture has increased notably in Latin America. Foreign investors, as much private as state, are interested in agricultural production, either for an expected benefit, or to assure the food supply. This increase in investment can be positive for the countries of the region. Nevertheless, in order to carry out this determination it is necessary to understand, among other things, the legal effects of these investment flows. This work maintains that the property rights acquired by foreign investors over the land and their agricultural undertakings may be different from the rights of national investors. This is because of foreign investment protection treaties. The strengthening of the rights of foreign investors affects the relationship between these investors and the receiving state. This article analyzes the effects of the rights of foreign investors in relation to five categories of state initiatives. Specifically, they are 1) the right to export production or the cost of exportation in the face of commercial and taxation measures; the right to continue a project in the face of changes within the regulatory paradigm; 3) the right to continue a project in the face of political change or new social preferences; 4) the right to receive better compensation in the face of agricultural reforms or programmes of historical reparation; 5) the right to maintain the business plan in the face of a food crisis.